2021
DOI: 10.1016/j.ajur.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of patients with ductal adenocarcinoma of the prostate receiving radical prostatectomy or radiotherapy

Abstract: Objective To evaluate the oncological outcomes of ductal adenocarcinoma of the prostate (DAC) managed with radical prostatectomy (RP) or radiotherapy (RT) and optimize the proper treatment modality to DAC comprehensively. Methods The cohorts included a total of 528 patients from the Surveillance, Epidemiology and End Results (SEER) database, 354 receiving RP and 174 receiving RT. Cox proportional hazards regressions were performed to assess cancer specific mortality (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is therefore timely that this issue of Asian Journal of Urology includes a report by Liu et al. [ 5 ] on the oncological outcomes of patients with DAC of the prostate treated with either radical prostatectomy or radiotherapy. They concluded that radical prostatectomy was associated with better survival outcomes in DAC, when compared to radiotherapy.…”
mentioning
confidence: 99%
“…It is therefore timely that this issue of Asian Journal of Urology includes a report by Liu et al. [ 5 ] on the oncological outcomes of patients with DAC of the prostate treated with either radical prostatectomy or radiotherapy. They concluded that radical prostatectomy was associated with better survival outcomes in DAC, when compared to radiotherapy.…”
mentioning
confidence: 99%